Silver Mesoporous Silica Nanoparticles: Fabrication to Combination Therapies for Cancer and Infection. Issue 4 (12th January 2022) - He, Xuan; Chen, Fangman; Chang, Zhimin; Waqar, Kasim; Hu, Hanze; Zheng, Xiao; Wang, Yingshuai; Dong, Wen‐fei; Yang, Chao
Abstract: The integration of silver nanoparticles (Ag NPs) with mesoporous silica nanoparticles (MSNs) protects the former from aggregation and promotes the controlled release of silver ions, resulting in therapeutic significance on cancer and infection. The unique size, shape, pore structure and silver distribution of silver mesoporous silica nanoparticles (Ag‐MSNs) embellish them with the potential to perform combined imaging and therapeutic actions via modulating optical and drug release properties. Here, we comprehensively review the recent progress in the fabrication and application of Ag‐MSNs for combination therapies for cancer and infection. We first elaborate on the fabrication of star‐shaped structure, core‐shell structure, and Janus structure Ag‐MSNs. We then highlight Ag‐MSNs as a multifunctional nanoplatform to surface‐enhanced Raman scattering‐based detection, non‐photo‐based cancer theranostics and photo‐based cancer theranostics. In addition, we detail Ag‐MSNs for combined antibacterial therapy via drug delivery and phototherapy. Overall, we summarize the challenges and future perspectives of Ag‐MSNs that make them promising for diagnosis and therapy of cancer and infection. Abstract : The integration of silver nanoparticles (Ag NPs) with mesoporous silica nanoparticles (MSNs) protects the Ag NPs from aggregation and promotes controlled release of silver ions, embellishing combination of imaging and therapeutic actions via modulating optical and drug release properties. Here, we comprehensively review the recent progress in the fabrication and application of Ag‐MSNs for combination therapies for cancer and infection. Overall, we summarize the challenges and future perspectives of Ag‐MSNs that make them promising for diagnosis and therapy of cancer and infection.